Memaknai Fakta dan Klarifikasi: Orientasi Epistemik Fact-Checking Kampus di Asia Tenggara - Ahmad Fadhli; Santi Indra Astuti; Alexandria Cempaka Harum; Tresna Wiwitan; Rita Gani (Jurnal Inovasi Komunikasi, 2026)
Abstrak. The increasing spread of misinformation on social media has prompted a number of universities in Asia to develop campus-based fact-checking initiatives. This study analyzes the epistemic orientation of fact-checking practices within the ANNIE School Net network, a regional Southeast Asian campus newsroom program led by Masato Kajimoto. The study employs a qualitative method with a comparative case study approach, utilizing participatory observation at the 2024 ANNIE School Net Conference, analysis of program documents, and content analysis of campus fact-checking Instagram accounts in Indonesia, Malaysia, and Vietnam. The findings reveal two distinct epistemic orientations. First, a news-reactive model focused on verifying viral news and current socio-political claims, as seen in the initiatives from Malaysia and Vietnam. Second, a scientific-educative model emphasizing the debunking of popular myths through scientific clarification, as practiced by one university in Indonesia. These findings suggest that knowledge transfer within academic networks does not result in homogeneous practices but is negotiated through institutional contexts, pedagogical priorities, and socio-political considerations. This study offers a typology of epistemic orientations in campus fact-checking as a contribution to digital literacy research in Southeast Asia.